Effect of target change during the simple attack in fencing - Gutiérrez-Dávila, M.; Rojas, F. J.; Caletti, M.; Antonio, R.; Navarro, E. (Journal of Sports Sciences, 2013)
The aim of this study was to test the effect that changing targets during a simple long lunge attack in fencing exerts on the temporal parameters of the reaction response, the execution speed, and the precision and the coordination of the movement pattern. Thirty fencers with more than 10 years of experience participated in this study. Two force platforms were used to record the horizontal components of the reaction forces and thereby to determine the beginning of the movement. A three-dimensional (3D) system recorded the spatial positions of the 9 markers situated on the fencer plus the epee, while a moving target was projected on a screen, enabling the control of the target change. The results indicated that when a target change is provoked the reaction time (RT), movement time (MT), and the time used in the acceleration phase of the centre of mass (CM) increases significantly with respect to the attack executed with a straight thrust. The speed and horizontal distance reached by the CM at the end of the acceleration phase (VX(CM) and SX(CM), respectively) significantly decreased, while the errors increased. However, the temporal sequence of the movement pattern did not appreciably change.